Effect of intercropping oats with alfalfa on dry matter yield, nutritive value, in vitro ruminal fermentation kinetics and silage quality - Wana, Daniel (Jimma University, 2024)
Oats (Avena sativa L.) and alfalfa (Medicago sativa L.)) intercropping is a recent practice in Ethiopia. However, there is limited knowledge on the ideal planting density for oats and alfalfa when intercropped to achieve a mixture of high nutritional quality for use as animal feed. A field experiment was carried out to study the effect of seed ratio on yield components (total dry matter and seed), nutritional value (CP, OM, NDF, ADF, ADL and Ash), in vitro fermentation kinetics (gas production, short chain fatty acids), silage quality (physical and chemical properties) and soil improvement (PH, OC, OM, EC, CEC, TN, K, P) of oats and alfalfa grown in the pure stand and intercropping system. The experiment was conducted at the Adami Tulu Agricultural Research Center under irrigation conditions during February - June 2022/2023 in Adami Tulu Jiddo Kombolcha District, Oromia Regional State, Ethiopia. Treatments consisted of one adapted oats (bate) variety and one alfalfa (magna 788) accession in an additive design at three plant densities (25%, 50%, and 75% of their recommended sole seed rates of 80 and 15 kg per hectare for oats and alfalfa respectively) and the recommended 100% plant density of sole oats and sole alfalfa:T1¬-(sole oats), T2- (sole alfalfa), T3- (75% oats + 25%alfalfa), T4- (50% oats + 50% alfalfa), T5- (25% oats + 75% alfalfa) arrangement. The experiment was laid out in Randomized Complete Block Design (RCBD) with four replications. Results showed statistically significant differences (P<0.05) in all tested parameters of agronomic yield, chemical composition of forage and silage, soil improvement and fermentation kinetics data. The highest DMY (14.64t/ha) was recorded from T4, followed by T3 (14.51t/ha). OM, CP, Ash, NDF, ADF, ADL and IVDMD revealed significant variation (p<0.05) among the treatments both in forage and silage. OM and CP content of oats+alfalfa produced in intercrop particularly from T4 seed ratio(92.08 and 17.33) tends to be better due to alfalfa component in the intercrop than that of sole oats(92.03 and 11.53) but lower than pure stand of alfalfa(93.53 and 21.2)respectively. According to the results obtained, the total physical score of the silages, consisting of the sum of the smell, color, moldiness and structure scores ranged between 3.08-3.32 and the physical quality class of the silages ranged between middle-very good classes. It was determined that the silage DM, NDF, ADF and ADL ratios decreased, and the pH, OM and CP values increased statistically (P<0.05) in parallel with the increase in the alfalfa ratio in the mixture. The analysis of soil samples showed an increased level (P<0.05) of (OM, OC, EC, CEC, TN, K and P) of soil nutrients based on treatment combinations. All treatment groups indicated a slight change (P>0.05) in pH values above the initial recorded average value of 4.43 in the experiment. The pH of the soil after forage harvest was statistically higher(P<0.05) in sole oats (6.15) and sole alfalfa (6.3) than that of their mixtures. In vitro gas and methane production as well as short chain fatty acids were all statistically (P<0.05) affected by seeding ratio of oats with alfalfa with the highest values observed in sole alfalfa and followed by intercropped groups and the lowest in sole oats. Total gas production, methane and short chain fatty acids production increased with increasing proportion of alfalfa seed ratio in the mixture. While T1(sole oats) produced the lowest methane than other treatments. Generally, in the present study the seed ratio combinations of T4 and T3 were the best performing in most agronomic, nutritional values, improved soil fertility, fermentation properties of their silage and balancing gas and methane production both in forage and silage and it is recommended for fodder production in the studied area and related agro-ecology. Further studies should test the effect of oats and alfalfa intercropping on live animal performance.